Empowering Fisherwomen in Galesong: Responding to the Challenges of Dual Roles Through a Participatory Approach - A.Noer Chalifah Ramadhany; A. Octamaya Tenri Awaru; Zainal Arifin; Tiara Nur’aini (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Fisherwomen in Galesong, Takalar Regency, play a significant dual role in the socio-economic life of coastal communities. Not only do they help their husbands in their fishing activities, they also return to their domestic roles as housewives. This condition causes participants to face double pressure, which has a serious impact on their health, productive capacity, and socio-economic well-being. Through a participatory approach, this activity seeks to explore the problems experienced by fisherwomen and identify potentials that can be developed in their empowerment efforts. The methods used include participatory observation, interviews, and focus group discussions (FGD) with fisherwomen. Despite having high enthusiasm and fighting spirit to support family welfare, they are still hampered by limited access to information, training, and formal role legitimacy. From this activity, recommendations emerged to present community-based empowerment programs that respond directly to the realities faced by women.